PENGAWASAN DAN PENGENDALIAN SENJATA YANG BEREDAR DI MASYARAKAT (KAJIAN PARADIGMA NORMATIF DAN INTERPRETATIF DALAM KRIMINOLOGI) - Yusman, Herlin Eka (Katalogis, 2015)
The existence of firearms must be controlled by the State in order to avoid abuse, smuggling and illicit trafficking senjata api which can threaten the life of society and the state. Issues to be examined is how the supervision and control of firearms circulating in the community as well as the constraints. The purpose of writing is to know both these problems within the framework of providing social policy for the government to ensure citizens nyaaman of misuse of firearms. The approach used is to study sociology to law, this research is based on the paradigm of criminology who studied crime in its various aspects. System monitoring and control of firearms in circulation by the civil society is not organized in a centralized system that integrate or to facilitate checking and supervision. Constraints are weak supervision of the implementation regulation of firearms licensing. Similarly, monitoring for the existence Soft Gun and gun assemblies freely circulating in the community, so prone to be misused. This resulted in a sense of security in society can not be realizedeventoanincreaseincrime.